Macrophage migration inhibitory factor reduces apoptosis in cerebral arteriovenous malformations - Chen, Guangzhong; Zheng, Meng; Shu, Hang; Zhan, Shengquan; Wang, Hongqin; Zhou, Dong; Zeng, Shaojian; Tang, Kai; Feng, Lei (Neuroscience letters, 2012)
► We used the human AVM specimens as the research objects. ► We investigated the relationship between MIF, apoptosis and cleaved caspase-3 expression. ► It is the first time to show the abnormal apoptosis may be involved in the pathogenesis of brain AVM. ► The increased MIF expression may play an important role regulating the homeostasis of AVM vessels. Purpose: To investigate the expression of macrophage migration inhibitory factor (MIF) in human brain arteriovenous malformations (AVM). Materials and methods: Twelve AVM specimens were obtained from patients who did not received preoperative embolization. MIF levels were measured by Western blot and matrix metalloproteinase 9 (MMP9) levels were measured by reverse transcription PCR. The expression of MIF in brain AVMs was also evaluated by immunohistochemistry and was correlated with apoptosis and the expression of cleaved caspase-3 and MMP9. Results: The expression of MIF, MMP9, and cleaved caspase-3 was elevated in brain AVM vessels. High levels of MIF were primarily found in the endothelium and adventitia, whereas apoptotic cells were concentrated in the smooth muscle layer. Conclusions: Abnormal apoptosis may be involved in the pathogenesis of brain AVM. In addition, increased MIF expression could play an important role regulating the homeostasis of AVM vessels.